High Adherence to Antimalarials and Antibiotics under Integrated Community Case Management of Illness in Children Less than Five Years in Eastern Uganda - Kalyango, Joan N.; Rutebemberwa, Elizeus; Karamagi, Charles; Mworozi, Edison; Ssali, Sarah; Alfven, Tobias; Peterson, Stefan (PLoS ONE, 2013)
Development of resistance to first line antimalarials led to recommendation of artemisinin based combination therapies (ACTs). High adherence to ACTs provided by community health workers (CHWs) gave reassurance that community based interventions did not increase the risk of drug resistance. Integrated community case management of illnesses (ICCM) is now recommended through which children will access both antibiotics and antimalarials from CHWs. Increased number of medicines has been shown to lower adherence.
Keywords: Antimalarials; Antibiotics; Integrated Community Case Management; Illness; Children